[Other] Ways of Occupying Public Space - Ximena Ocampo Aguilar (Dearq, 2025)
[Other] Ways of Occupying Public Space is an architectural research project aimed at critically analyzing and reclaiming the everyday forms and actions that bring life to our cities and shape their public sphere. Using architecture as an ethnographic tool to explore and document complex spatial phenomena, the project has compiled an archive that records uses, objects, and actions of public space occupation—including those that are unintentional or unplanned. This documentation reveals that the city is a dynamic and ever-evolving space of tension, emphasizing the need for architecture to acknowledge its complexity and spontaneity.